Motivasi dan kepuasan kerja pegawai puskesmas BLUD dan non-BLUD Kabupaten Semarang - Aswindar Adhi Gumilang; Tri Pitara Mahanggoro; Qurrotul Aini (STIKes Surya Global Yogyakarta, 2018)
The public demand for health service professionalism and transparent financial management made some Puskesmas in Semarang regency changed the status of public health center to BLUD. The implementation of Puskesmas BLUD and non-BLUD requires resources that it can work well in order to meet the expectations of the community. The aim of this study is to know the difference of work motivation and job satisfaction of employees in Puskesmas BLUD and non-BLUD. Method of this research is a comparative descriptive with a quantitative approach. The object of this research are work motivation and job satisfaction of employees in Puskesmas BLUD and non-BLUD Semarang regency. This Research showed that Sig value. (P-value) work motivation variable was 0.019 smaller than α value (0.05). It showed that there was a difference of work motivation of employees in Puskemas BLUD and non-BLUD. Sig value (P-value) variable of job satisfaction was 0.020 smaller than α value (0.05). It showed that there was a difference of job satisfaction of BLUD and non-BLUD. The average of non-BLUD employees motivation were 76.59 smaller than the average of BLUD employees were 78.25. The average of job satisfaction of BLUD employees were 129.20 bigger than the average of non-BLUD employee were 124.26. Job satisfaction of employees in Puskesmas BLUD was higher than non-BLUD employees.